2006
DOI: 10.1128/iai.74.2.861-868.2006
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Mycobacterium tuberculosis α-Crystallin-Like hspX Gene Causes Increased Bacterial Growth In Vivo

Abstract: Hypervirulent mutants of Mycobacterium tuberculosis, whose growth rates are higher in vivo, have now been reported to have mutations in both regulatory and structural genes, but the basis for this unusual phenotype is not understood. One hypervirulence gene, dosR (devR, Rv2031c), activates transcription of approximately 50 genes in this pathogen in response to hypoxia and nitric oxide stress. The most dramatic activation (ϳ80-fold) is activation of the hspX (acr, Rv2031c) gene, which encodes a 16-kDa ␣-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
120
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 58 publications
5
120
2
4
Order By: Relevance
“…35 S]methionine labeling studies Hu et al, (2006) showed that in dormant MTB culture maintained in unstirred screw-cap tubes for 50 days, protein synthesis decreased by 98% (42). Eighty-six proteins involved in protein synthesis were detected in our study.…”
Section: Validation Of Quantitative Proteomic Data By Qpcr-tomentioning
confidence: 48%
See 1 more Smart Citation
“…35 S]methionine labeling studies Hu et al, (2006) showed that in dormant MTB culture maintained in unstirred screw-cap tubes for 50 days, protein synthesis decreased by 98% (42). Eighty-six proteins involved in protein synthesis were detected in our study.…”
Section: Validation Of Quantitative Proteomic Data By Qpcr-tomentioning
confidence: 48%
“…This protein is implicated in the survival of MTB inside macrophages (15). The biology of alpha-crystallin 1 is complex as evidenced by the adverse effect of the gene knockout on growth (69). Overexpression of acr slows down the growth rate of MTB and the autolysis of post-stationary phase cultures (15).…”
Section: Validation Of Quantitative Proteomic Data By Qpcr-tomentioning
confidence: 99%
“…The hspX gene has been found to be upregulated during the stationary phase (37), in several models of dormancy (23,37), and during the growth of M. tuberculosis in macrophages (30), mice (31), and lung specimens from patients with TB (34). Recent work has demonstrated that HspX has a role in slowing the growth of M. tuberculosis both in vitro and in vivo (14). An hspX gene replacement mutant of M. tuberculosis exhibited increased growth in macrophages and also in a mouse model, whereas overexpression of the hspX gene resulted in a reduction in the growth rate of M. tuberculosis in vitro (14,39).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has demonstrated that HspX has a role in slowing the growth of M. tuberculosis both in vitro and in vivo (14). An hspX gene replacement mutant of M. tuberculosis exhibited increased growth in macrophages and also in a mouse model, whereas overexpression of the hspX gene resulted in a reduction in the growth rate of M. tuberculosis in vitro (14,39). The demonstration that expression of hspX was induced during slow growth in a carbon-limited chemostat provides further evidence that this chaperone plays a role in reducing the growth rate of M. tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that expression of the 16-kDa M. tuberculosis ␣-crystallin protein, Acr, encoded by acr (also called hspX, Rv2031c) occurs in vivo (13,18,43,53) and is rapidly induced during stationary-phase growth, in unagitated submerged cultures, and in oxygen-limiting or nitric oxide (NO)-enriched microenvironments (9,10,17,22,34,42,48,52,53). acr is a member of the DevR (also called DosR) "dormancy" regulon that includes genes that are positively regulated in response to hypoxia and/or low levels of NO (28,31,41,42,47).…”
mentioning
confidence: 99%